Stem cell homing as a promising strategy for bone regeneration: focus on biomaterials - SB Liu; Y Liu; ZZ Zheng; BL Li; JJ Shao; X Liu; E Luo; HH Liu (European Cells & Materials)
Bone regeneration, predominantly orchestrated via stem cell, holds significant implications for orthopedic and reconstructive surgery. Owing to the inherent limitations associated with stem cell transplantation and related modalities, the strategy of biomaterial-mediated endogenous stem cell homing has emerged as a promising alternative, which has garnered substantial interest from both the academic and clinical communities. This innovative approach employs chemokines and other molecular cues to direct the recruitment of endogenous stem cells to the site of bone defect, thereby promoting bone regeneration in a more physiologically relevant manner. Bone marrow is recognized as the primary niche and a major reservoir for a diverse array of stem cells. In this comprehensive review, we meticulously delineate the endogenous stem cell homing paradigm and describe the biological factors affecting stem cell homing. Moreover, we provide an in-depth analysis of the latest developments in functionally enriched biomaterials that are specifically designed to facilitate the homing, survival, and functional integration of stem cell at the site of bone injury.